KEBERTERIMAAN KALIMAT DALAM PIDATO ANIES BASWEDAN - Heny Sulistyowati; Endik Tri Lutfi (STKIP PGRI Jombang, 2019)
Society as social creature is able to live interacting and able to adjust good and bad behavior based on the condition of their social environment. The theory of sociology is as a form of understanding of good and bad human behavior. Like this study, in order to reach the research object that it is necessary to use the deepening of the literary sociology theory.This studytakes novel as object that aims to facilitate researcher doing on research by referring to indicator of the moral aspect which exist in the focus of the research in Dilan 1990 novel: (1) human relation with oneself and (2) human relation with other. This study is descriptive qualitative study. The subject of this study is Dilan 1990 novel by Pidi Baiq. This study is focused on issues relates to the moral aspect with theliterary sociology study. The data used is in the form of word and written sentence (Text) that exists in Dilan 1990 novel. Data research procedures are done through reading, coding, collecting, description, analysis, and data conclusion. The result shows that there are moral valuesin Dilan 1990 novel by Pidi Baiq relates to: (1) human relation with oneself which includes: responsibility and emotional, (2) human relation with other which includes: discipline, crime, love, and caring or empathy.